Comparative Analysis Of Star And Mesh Topologies In Computer Networks Based On Literature Study - Rizki Aditya Putra; Raffi Sulistyo Permana Putra; Zah Rahan Aprilianto (PT Mekar Research and Publishing, 2026)
The development of information technology requires the availability of computer networks that are fast, stable, secure, and easy to manage. One important factor in network design is the selection of a network topology that suits organizational needs. Network topology determines the relationships between devices, data communication paths, installation costs, and ease of maintenance. This study aims to analyze the comparison between two commonly used network topologies, namely Star and Mesh topologies, based on two scientific journals discussing their respective implementations. The research method uses a literature study with a descriptive comparative approach. The results of the study indicate that the Star topology has advantages in terms of ease of installation, low cost, simple management, and is suitable for small to medium-scale Local Area Networks (LAN). In contrast, the Mesh topology excels in redundancy with multiple alternative paths, fault tolerance, security, flexibility, and scalability, making it more suitable for modern wireless networks and environments requiring high network availability. The conclusion shows that there is no universally best topology; instead, the choice must be adjusted to user needs, budget, and implementation scale.